Identification of Secondary Metabolites and Antibacterial Activity of Non Polar Fraction from Heterotrigona itama Propolis - Abdul Aziz; Veggy Nadya Yuliawan; Paula Mariana Kustiawan (Journal of Fundamental and Applied Pharmaceutical Science, 2021)
Propolis is one of the natural products produced by kelulut bees and is still not widely used. The type of stingless bee that is the prima donna in the community is Heterotrigona itama. This study aims to determine the phytochemical content of the n-hexane fraction of Heterotrigona itama bee propolis collected from Kutai Kartanegara, East Kalimantan. The n-hexane fraction was obtained from the methanol extract of H. itama propolis by the liquid-liquid partition method. After obtaining the n-hexane fraction, the research continued with a qualitative phytochemical test to identify the compound and determine total phenolic. Antibacterial activity was determined by the agar well diffusion method with a serial concentration in Escherichia coli bacteria. Qualitative phytochemical analysis in the form of color changes showed that the n-hexane fraction of H. itama propolis contained flavonoids, alkaloids, saponins, and tannins. Based on the results, the total phenolic content of the n-hexane fraction sample was 490 mgGAE/100 g. It caused the n-hexane fraction to have lower phenolic content than the methanol extract (792 mg GAE100 g). Furthermore, this result indicated that the non-polar fraction was not substantial enough to extracted phenolic compounds. It correlated to the antibacterial activity of the n-hexane fraction, which was very weak (2  mm ± 1.5) at  200µg/mL concentration.